2022
DOI: 10.1080/07853890.2022.2083671
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of systemic inflammatory response index in patients with acute coronary syndrome undergoing percutaneous coronary intervention

Abstract: Background The systemic inflammatory response index (SIRI) is a novel inflammatory biomarker in many diseases. Objectives The aim of this study was to examine the association between SIRI and adverse events in patients with the acute coronary syndrome (ACS) undergoing percutaneous coronary intervention. Methods A total of 1724 patients with ACS enrolled from June 2016 to November 2017 at a single centre were included in this study, and SIRI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 54 publications
(52 reference statements)
6
67
0
Order By: Relevance
“…In a 10-year observation, SIRI was found to have an association with CVD occurrence [ 41 ] and an increased risk of supraventricular tachycardia in patients with a history of stroke [ 42 ]. In patients who underwent percutaneous coronary intervention (PCI) due to ACS, SIRI was an independent predictor of MACE [ 29 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a 10-year observation, SIRI was found to have an association with CVD occurrence [ 41 ] and an increased risk of supraventricular tachycardia in patients with a history of stroke [ 42 ]. In patients who underwent percutaneous coronary intervention (PCI) due to ACS, SIRI was an independent predictor of MACE [ 29 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several inflammatory indexes, such as, C-reactive protein, NLR, interleukins, have been demonstrated to be predictive of short- or long-term prognosis in patients with STEMI [ 24 28 ]. Recent studies had demonstrated the positive relationship between SIRI and prognosis information in different subject cohorts [ 14 16 , 18 , 29 ]. For instance, Xu et al conducted a multi-center retrospective analysis of 1,499 rheumatoid arthritis (RA) patients, and determined that SIRI is significantly related to the disease activity of RA, even can predict the tumor development of RA individuals [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…MI was considered as [ 1 ] symptoms of ischemic chest pain; [ 2 ] a characteristic ST-T dynamic evolution on the electrocardiogram, or with abnormal q waves; [ 3 ] serum myocardial enzyme spectrum increased and decreased. Nonfatal MI was diagnosed as new pathological Q waves in ≥ 2 contiguous electrocardiogram leads according to the previous study [ 13 ]. Patients with an acute ischemic cerebral vascular event were diagnosed with stroke, and any nonstaged revascularization after PCI was considered URR (Fig.…”
Section: Methodsmentioning
confidence: 99%